Liberty before Liberalism:: The Case of Francisco Suárez - Macedo, Paulo Emílio Vauthier Borges de (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
Francisco Suárez was one of the most important Theologians of the Spanish Scholasticism and, in the 20th century, a growing strand of lawyers has acknowledged his contributions to the origin of International Law. However, his Legal Philosophy has been relegated, despite the fact that he had expounded ideas so revolutionary that they were forbidden in England, France and ultimately even Spain. Time has cursed and forgotten Francisco Suárez because he supported Classical Liberalism almost a century before the Britons. Human rights, the social contract and limits to the State’s (and even to the Pope’s) power were concepts too bold for a late Sixteenth-century Catholic Spaniard.